2017
DOI: 10.19173/irrodl.v18i4.3120
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education Faculty Perceptions of Open Textbook Adoption

Abstract: The high cost of tuition and textbooks can have a negative impact on potential students from lower Specifically, this study uses the COUP framework to examine: (1) cost reduction, (2) outcomes, (3) uses, and (4) the faculty perceptions of the quality of OpenStax textbooks. Additionally, we expanded the framework to address (5) the relationship between the perceived quality of the OpenStax textbook and the faculty perception of student performance, (6) the faculty's intention to continue to adopt OpenStax textb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 10 publications
4
39
0
Order By: Relevance
“…Generally, visual aspects of the textbook, namely, appeal and use of photographs, were higher for the commercial textbook compared to the open textbook. This converges with previous faculty reviews of open textbooks that the graphics quality was not as good as in commercial counterparts (Jung et al, 2017). However, because of their licensing, open textbooks are typically customizable (Wiley et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Generally, visual aspects of the textbook, namely, appeal and use of photographs, were higher for the commercial textbook compared to the open textbook. This converges with previous faculty reviews of open textbooks that the graphics quality was not as good as in commercial counterparts (Jung et al, 2017). However, because of their licensing, open textbooks are typically customizable (Wiley et al, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Few texts employed pre-assessments. This heuristic approach of evaluating texts using instructional design principles needs to be balanced by comparing quality ratings to faculty and student ratings of open textbooks as in other studies (e.g., Jung, Bauer, & Heaps, 2017;Vander Waal Mills et al, 2019) and to the results of efficacy studies (e.g., Hilton, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of studies referencing faculty and student ratings consistently reported positive ratings of open textbooks by faculty and students (Bliss, Hilton, Wiley, & Thanos 2013;Jung, Bauer, & Heaps 2017;Vander Waal Mills, Gucinski, & Vander Waal 2019). Similarly, in a review of efficacy research on OER and pen Textbooks, Hilton (2016) found that OER were at least as effective as licensed materials at promoting student achievement.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…This ability to customize OER is an advantage of OER use for instructors (Belikov & Bodily, 2016), and adaptations may be done to make OER content accessible for learners with disabilities (Rice, 2019). Most instructors simply adopt OER as-is, and provide students with a link to existing resources (Jung, Bauer, & Heaps, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Both authors are formally trained as instructional designers and have substantial experience designing instructional content for a wide range of media and contexts, including online instruction in the university setting. Thus we felt confident that given time and effort we would be able to accomplish this task, and joined the minority of instructors who have created their own open textbooks (Jung et al, 2017).…”
Section: Project Contextmentioning
confidence: 99%